Intestinal invagination in the adult. Case report - Almada, Mario; Minasián, Pablo; Caviglia, Pablo (Cirugía del Uruguay, 2020)
Itussusception is a rare cause of intestinal occlusion in adults. The clinical case of this condition in an older adult is presented. In this case, computed tomography (CT) identified intussusception and the treatment was an intestinal resection. Pathological anatomy provided the definitive diagnosis. The most frequent etiology of the obstruction corresponds to malignant organic lesions at the level of the colon, and benign in the small intestine. Preoperative diagnosis has now increased, thanks to the advancement of imaging tests. Intestinal resection continues to be the treatment in most cases, due to the high percentage of malignant pathology as the underlying cause.